Informed consent for case reports – an ethical perspective - Santos, Paulo; Hespanhol, Alberto (Acta Bioethica, 2017)
The case report is a special type of scientific publication that focuses on a single patient, raising problems of confidentiality, as the exposure of the intimacy may facilitate identification of the participants. The legitimacy for the public disclosure derives from the informed consent, ensuring the preservation of patients’ self-determination. In this article, we discuss aspects of autonomy as basic ethical principle, framing under the Portuguese Law. In the case reports, as in any clinical investigation, the will of the patient should prevail over the interests of research and researchers, even when he is unable to consent, like the minors, the disabled or the deceased, enforcing the legal rules and addressing to the active involvement of the guardians and the relatives.